No leaves in autumn [large type] - Wangard, Terri (Wangard, Terri. Unsung stories of World War II, 2025)
"Marie Foubert grew up in an orphanage and struggles with feelings of rejection. As a Red Cross recreation worker, she interacts with the American men based in Iceland during World War II. Her growing attraction to seaplane pilot Stefan Dabrowski excites and concerns her. Won't he disappear from her life like everyone else? Stefan hears his commanding officer describe him as "exciting as last night's bathwater." One of his colleagues constantly berates him because of his Polish heritage. Despite being the squadron's most productive pilot, he is threatened with court martial. A showdown approaches to prove who's the better pilot and the better man. Meanwhile, Marie's cousin, passing through Iceland, tries to see her after spotting her photo in Life magazine. She declines to meet him, but Stefan encourages her to do so and learn why her family abandoned her all those years ago. Marie may yet gain a family after all."--